Machine learning predictive model for aspiration risk in early enteral nutrition patients with severe acute pancreatitis - Bo Zhang; Huanqing Xu; Qigui Xiao; Wanzhen Wei; Yifei Ma; Xinlong Chen; Jingtao Gu; Jiaoqiong Zhang; Lan Lang; Qingyong Ma; Liang Han (Heliyon)
Background: The aim of this study was to build and validate a risk prediction model for aspiration in severe acute pancreatitis patients receiving early enteral nutrition (EN) by identifying risk factors for aspiration in these patients. Methods: The risk factors for aspiration were analyzed to build a prediction model based on the data collected from 339 patients receiving enteral nutrition. Subsequently, we used six machine learning algorithms and the model was validated by the area under the curve. Results: In this study, the collected data were divided into two groups: a training cohort and a validation cohort. The results showed that 28.31 % (77) of patients had aspiration and 71.69 % (195) of patients had non-aspiration in training cohort. Moreover, age, consciousness, mechanical ventilation, aspiration history, nutritional risk and number of comorbidities were included as predictive factors for aspiration in patients receiving EN. The XGBoost model is the best of all machine learning models, with an AUROC of 0.992 and an F1 value of 0.902. The specificity and accuracy of XGBoost are higher than those of traditional logistic regression. Conclusion: In accordance with the predictive factors, XGBoost model, characterized by excellent discrimination and high accuracy, can be used to clinically identify severe acute pancreatitis patients with a high risk of enteral nutrition aspiration. Relevance to clinical practice: This study contributed to the development of a predictive model for early enteral nutrition aspiration in severe acute pancreatitis patients during hospitalization that can be shared with medical staff and patients in the future. No patient or public contribution: This is a retrospective cohort study, and no patient or public contribution was required to design or undertake this research.